2011
DOI: 10.1073/pnas.1103964108
|View full text |Cite
|
Sign up to set email alerts
|

Ineffective erythropoiesis with reduced red blood cell survival in serotonin-deficient mice

Abstract: Serotonin (5-HT) has long been recognized as a neurotransmitter in the central nervous system, where it modulates a variety of behavioral functions. Availability of 5-HT depends on the expression of the enzyme tryptophan hydroxylase (TPH), and the recent discovery of a dual system for 5-HT synthesis in the brain (TPH2) and periphery (TPH1) has renewed interest in studying the potential functions played by 5-HT in nonnervous tissues. Moreover, characterization of the TPH1 knockout mouse model (TPH1 mice provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 45 publications
6
57
1
1
Order By: Relevance
“…78 We revealed a pivotal role for 5-HT in erythropoiesis and red blood cell survival using the Tph1−/− KO mouse. 79 Our data established that 5-HT regulates in vivo erythropoiesis as 5-HT−deficient animals present a phenotype of macrocytic anemia due to an ineffective erythropoiesis. In the bone marrow, absence of 5-HT down-regulates the rate of red blood cell production since erythroid precursors progression toward terminal differentiation is hampered.…”
Section: ■ Serotonin and Red Blood Cell Production And Survivalmentioning
confidence: 82%
See 1 more Smart Citation
“…78 We revealed a pivotal role for 5-HT in erythropoiesis and red blood cell survival using the Tph1−/− KO mouse. 79 Our data established that 5-HT regulates in vivo erythropoiesis as 5-HT−deficient animals present a phenotype of macrocytic anemia due to an ineffective erythropoiesis. In the bone marrow, absence of 5-HT down-regulates the rate of red blood cell production since erythroid precursors progression toward terminal differentiation is hampered.…”
Section: ■ Serotonin and Red Blood Cell Production And Survivalmentioning
confidence: 82%
“…In vitro experiments with isolated Tph1−/− erythroid precursors showed they have a decreased proliferative capacity, that is restored by addition of 5-HT, suggesting they possess the capacity to synthesize 5-HT. 79 Further evidence to support a direct role for 5-HT in erythroid cells came from binding experiments demonstrating the presence of 5-HT 2A and 5-HT 2B receptors and SERT on erythroid precursors. On the basis of our data, although the definitive presence of Tph1 has yet to be proven, we propose that a local paracrine/autocrine serotonergic network exists in erythroid cells.…”
Section: ■ Serotonin and Red Blood Cell Production And Survivalmentioning
confidence: 99%
“…20 Recently, the absence of 5-HT was shown to reduce erythroid precursors in BM via 5-HT 2A and 5-HT 2B Rs because a 5-HT 2 agonist, PNU 22394, produced the same proliferative effect on erythroid precursors as observed with 5-HT. 28 At early stages of megakaryocytopoiesis, 5-HT regulates proliferation and survival by antiapoptotic effects on megakaryoblastic cells. 40 On megakaryocytic cell line HEL, pretreatment with 5-HT protected subsequent nitric oxide-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…20,28 We have assessed the effect of 5-HT 2B R blockade using the selective antagonist, RS-127445, during the differentiation of total BM cell cultures from mice. When mice BM was used in methylcellulose colony-forming assay, we observed a significant reduction in both CFU-GEMM/CFU-GM and CFU-E/BFU-E colonies with the 5-HT 2B R antagonist ( Figure 4A).…”
Section: Alterations Of Bm Differentiation After 5-ht 2b R Inhibitionmentioning
confidence: 99%
“…Together, these differences make a direct comparison difficult. More recently, an intriguing study demonstrated the importance of 5-HT in effective erythropoiesis, where the absence of 5-HT decreased differentiation of erythroid precursors and increased phagocytosis of erythrocytes (46). Like apoptotic cells, aging erythrocytes externalize phosphatidylserine on their outer membrane allowing them to be recognized and removed by phagocytes (47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%